1992
DOI: 10.1177/002224379202900303
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Providers and Users of Market Research: The Dynamics of Trust within and between Organizations

Abstract: The authors investigate the role of trust between knowledge users and knowledge providers. The kind of knowledge of special concern is formal market research. Users include marketing and nonmarketing managers; providers include marketing researchers within a user's own firm and those external to the firm. A theory of the relationships centering on personal trust is developed to examine (1) how users’ trust in researchers influences various relationship processes and the use of market research and (2) how the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
1,741
0
137

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 2,034 publications
(1,994 citation statements)
references
References 32 publications
31
1,741
0
137
Order By: Relevance
“…Trust is one of the topics that have attracted 310 Yu-Shan Chen major interest in the academic community. This is due to the fact that trust is thought as a strategic action in the marketing field and an essential ingredient in the success of relationships (Flavián et al, 2005;Moorman et al, 1992). Furthermore, to trust a brand implicitly implies that there is a high probability or expectancy for its consumers such that the brand would obtain positive evaluation.…”
Section: Green Marketingmentioning
confidence: 99%
See 1 more Smart Citation
“…Trust is one of the topics that have attracted 310 Yu-Shan Chen major interest in the academic community. This is due to the fact that trust is thought as a strategic action in the marketing field and an essential ingredient in the success of relationships (Flavián et al, 2005;Moorman et al, 1992). Furthermore, to trust a brand implicitly implies that there is a high probability or expectancy for its consumers such that the brand would obtain positive evaluation.…”
Section: Green Marketingmentioning
confidence: 99%
“…Considering brand trust as expectancy, it is based on the consumer's belief that the brand is consistent, competent, honest, and responsible (Doney and Cannon, 1997). Social exchange theory indicated that customer trust would enhance the social embeddedness of the consumerprovider relationship to further increase the customer's commitment to the relationship (Grayson and Ambler, 1999;Moorman et al, 1992;Singh and Sirdeshmukh, 2000). Brand equity is considered as a relational market-based asset, and it is attached to a brand and embeds in the relationships with its customers (Srivastava et al, 1998).…”
Section: Green Marketingmentioning
confidence: 99%
“…Based on business literature (Deshpandé & Zaltman, 1982;Maltz & Kohli, 1996;Menon & Varadarajan, 1992;Menon, Wilcox, & Maltz, 1999;Moorman, Deshpandé, & Zaltman, 1993;Moorman, Zaltman, & Deshpandé, 1992), a model was developed of some of the major antecedents and consequences of CI usage in firms. The model is summarized in Figure 1 and the definitions of each construct are provided in Table 2.…”
Section: The Modelmentioning
confidence: 99%
“…Establishing and maintaining a customer-driven organization in a business environment characterized by shorter product-life cycles, heightened global competition, changing supplier relationships, and new strategic alliances has fueled an increasing managerial and academic interest in the effective use of market information (Deshpande, 1982;Deshpande & Zaltman, 1982, 1984, 1987Menon & Varadarajan, 1992;Moorman, Zaltman, & Deshpande, 1992;Myers, Massy, & Greyser, 1980). Indeed, organizational generation, dissemination, and responsiveness to market intelligence are conceived as integral elements of a market orientation (Narver & Slater, 1990;Slater & Narver, 1994).…”
mentioning
confidence: 99%
“…The first stream has examined the nature of the research problem, the nature of the information, characteristics of the organization, the relationship between research results and the user of research, and the relationship between the researcher and the user of research findings (e.g., Deshpande & Zaltman, 1982, 1984, 1987Lee, Acito, & Day, 1987;Moorman, Deshpande, & Zaltman, 1993;Moorman, Zaltman, & Deshpande, 1992).…”
mentioning
confidence: 99%